Analisis Sistem Antrian Pada Proses Pelayanan Konsumen di Warung Lesehan - Harahap, Fadilla Arba; Rahma, Aulia; Rubaini, Mingle Oktaria; Ritonga, Irmayanti (Universitas Labuhanbatu, 2024)
The purpose of analyzing the queuing system in the process of customer service in warung lesehan is to evaluate the performance of the service queuing system in Warung Lesehan so as to obtain a decrease in the number of consumer queues. The method of research approach used is descriptive qualitative with data collection techniques through: observation, interviews and documentation with data analysis using Multi ChannelSingle Phase (M/M/1). It can be seen that warung lesehan uses queue model (M/M / 1). The queue structure used is a Single ChannelSingle Phase with only one server and one stage of Service.Usability level of warung lesehan service section = 0.83, the average number in the queue = 4.17/minute, the average number in the system = 5 minutes, the average waiting time in the queue = 0.08/minute, the average waiting time in the system = 0.1 / minute.. It is expected that warung lesehan can further optimize the service performance of each customer, so that customer waiting times are not too long,which makes sales decrease and affect customer arrivals, so queues can still be controlled and there is no buildup of long queues.